2018
DOI: 10.1128/aem.00657-18
|View full text |Cite
|
Sign up to set email alerts
|

Protein- and RNA-Enhanced Fermentation by Gut Microbiota of the Earthworm Lumbricus terrestris

Abstract: Earthworms are a dominant macrofauna in soil ecosystems and have determinative effects on soil fertility and plant growth. These invertebrates feed on ingested material, and gizzard-linked disruption of ingested fungal and bacterial cells is conceived to provide diverse biopolymers in the anoxic alimentary canals of earthworms. Fermentation in the gut is likely important to the utilization of ingested biopolymer-derived compounds by the earthworm. This study therefore examined the fermentative responses of gut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 73 publications
5
32
0
Order By: Relevance
“…4). This finding is consistent with other studies that have indicated that this taxon is not responsive during gut content fermentation (Meier et al, 2018;Zeibich et al, 2018). This finding is consistent with other studies that have indicated that this taxon is not responsive during gut content fermentation (Meier et al, 2018;Zeibich et al, 2018).…”
Section: Functional Perspectives Of An Ancient Gut Ecosystemsupporting
confidence: 93%
See 4 more Smart Citations
“…4). This finding is consistent with other studies that have indicated that this taxon is not responsive during gut content fermentation (Meier et al, 2018;Zeibich et al, 2018). This finding is consistent with other studies that have indicated that this taxon is not responsive during gut content fermentation (Meier et al, 2018;Zeibich et al, 2018).…”
Section: Functional Perspectives Of An Ancient Gut Ecosystemsupporting
confidence: 93%
“…S2A and Table S5). S3A) corroborated previous findings that revealed a positive response of these taxa to anoxia and endogenous gut nutrients (Zeibich et al, 2018(Zeibich et al, , 2019. S3A) corroborated previous findings that revealed a positive response of these taxa to anoxia and endogenous gut nutrients (Zeibich et al, 2018(Zeibich et al, , 2019.…”
Section: Effect Of Polysacharides On Fermentative Bacterial Familiessupporting
confidence: 90%
See 3 more Smart Citations